The impact of chronotype on VO2max in university students at two different times of the day - Moazzam Hussain Khan; Saurabh Sharma; Mohammed Essa Alsubaiei; Ahmad Sahely; Shibili Nuhmani (IP Iermakov S.S., 2023)
Background and Study Aim. To choose the ideal training or performance times, it is crucial to assess VO2 max performance across different time-of-day particular chronotypes. This study aimed to investigate the differences in VO2 max between the chronotype of university students during the morning and evening time of the day. Material and Methods. Fifty-two university students (26 morning type and 26 evening type) with mean age 23.05± 2.07 years, weight 66.71±4.31Kg and height of 170.90±5.18 cm and BMI of 22.75±1.91kg/m2 were recruited based on the results of the Horne-Ostberg Morningness- Eveningness Questionnaire (MEQs) participated in this Cross-over study. VO2 max was measured directly by gas collected using mouth tube breath to breath through the use of the gas analyzer the AD instrument (model-ML206) with an incremental graded maximal exercise test done on the treadmill. Results. The morning type group's VO2 max was significantly better in the morning hour than it was in the evening (p=.013), and when the VO2 max of the evening type group was measured in the morning and evening hours and compared, there was a statistically significant difference in favour of the evening hours (p=.004). Additionally, there is no discernible difference between the VO2 max of the morning type and the evening type group either in the morning hours or the evening hours, but trends indicate that the morning type group has a higher VO2max in the morning hour and the same is true for the evening type group in the evening hour. Conclusion. The findings of this study showed an interaction between chronotype and time of the day in VO2 max. For endurance training, trainers should consider the individual's chronotype and time of the day for exercise prescription.